IMPLEMENTATION OF THE 6th GRADE TEACHING CAMPUS AT STATE PRIMARY SCHOOL 101942 WORKSHOP: PELAKSANAAN KAMPUS MENGAJAR ANGKATAN 6 DI SD NEGERI 101942 BENGKEL - Putri, Ervina; Yanti Parinduri, Ramadha (UPMI Proceeding Series, 2024)
Merdeka Belajar is an idea launched by Nadiem Makarim who is the Minister of Education and Culture to produce superior Human Resources (HR) by prioritizing character education. The aim is to create students who are critical, creative, collaborative and skilled. The Batch 6 Campus Teaching Program is part of the Independent Campus Program which involves students from various educational backgrounds on each campus to support the teaching and learning process in schools, especially the facilities and infrastructure continuing to be left behind, infrastructure, teachers, limited access and so on, especially 3T (Disadvantaged, Frontier, Outermost) areas at primary and secondary school levels, as well as providing opportunities for them to learn and progress through activities outside the classroom. The teaching campus program will last for 4 months from 14 August to 5 December 2023. The implementation of the teaching campus program focuses on literacy, numeracy, technological adaptation and school administration support to ensure education continues and develops, especially considering the impact of the last pandemic. This is one of the guidelines from the Minister of Education and Culture. Independent learning is a process where the greatest potential is realized by teachers and students to innovate and improve the quality of independent learning. Presenting students as part of strengthening literacy and mathematics learning as well as teacher partners in implementing creativity and innovation in learning. One of the assisted schools that focuses on improving the quality of education is SD Negeri 101942 Bengkel.